Neutrino-dominated Relativistic Viscous Accretion Flows around Rotating Black Holes with Shocks - Amit Kumar; Sayan Chakrabarti; Santabrata Das (The Astrophysical Journal)
We investigate the relativistic, viscous, advective neutrino-dominated accretion flows (NDAFs) around rotating stellar-mass black holes, incorporating neutrino cooling. By adopting an effective potential to describe the spacetime geometry around the rotating black holes, we self-consistently solve the governing NDAF equations to obtain global transonic accretion solutions. Our findings indicate that, depending on the model parameters, namely, energy ( ε ), angular momentum ( λ ), accretion rate ( $\dot{m}$ ), viscosity ( α ), and black hole spin ( a _k ), NDAFs may harbor standing shocks where the Rankine–Hugoniot shock conditions are satisfied. Utilizing these shock-induced NDAF solutions, we compute the neutrino luminosity ( L _ν ) and neutrino annihilation luminosity ( ${L}_{ν \bar{ν }}$ ) across a wide range of model parameters. We further calculate maximum neutrino luminosity ( ${L}_{ν }^{{\rm{\max }}}$ ) and neutrino annihilation luminosity ( ${L}_{ν \bar{ν }}^{{\rm{\max }}}$ ), resulting in ${L}_{ν }^{{\rm{\max }}}\sim 1{0}^{51-53}$ erg s ^−1 (10 ^48−51 erg s ^−1 ) and ${L}_{ν \bar{ν }}^{{\rm{\max }}}\sim 1{0}^{48-52}$ erg s ^−1 (10 ^42−49 erg s ^−1 ) for a _k = 0.99 (0.0). These findings suggest that shocked NDAF solutions are potentially promising to explain the energy output of gamma-ray bursts (GRBs). We employ our NDAF model formalism to elucidate ${L}_{ν \bar{ν }}^{{\rm{obs}}}$ for five GRBs with known redshifts and estimate their accretion rate ( $\dot{m}$ ) based on the spin ( a _k ) of the central source of the GRBs studied here.